Réponses

Meilleure réponse !
2013-09-08T15:32:02+02:00
A=3(x-2)-5(x+3)=3x-6-5x-15=-2x-21

B=(2x-3)(3x-1)=6x^2-2x-9x+3=6x^2-11x+3

C=2a+3-(a+2)(a-3)=2a+3-a^2+3a-2a+6=-a^2+3a+9

D=(x+4)^2=(x+4)(x+4)=x^2+4x+4x+16=x^2+8x+16

E=(2-b)^2=(2-b)(2-b)=4-2b-2b+b^2=b^2-4b+4

F=(5x-1)^2=(5x-1)(5x-1)=25x^2-5x-5x+1=25x^2-10x+1
2013-09-08T15:36:46+02:00
A = 3x -6 -5x -15
A = -2x -21

B = 6x au carré -2x -9x +3
B = 6x au carre -11x +3

C = 2a + 3 -( a au carre +2a -3a -6 )
C = 2a + 3 - a au carré - 2a +3a +6
C = a au carre + 3a + 9

D = x au carré +8x + 16

E = 4 - 4b + b au carre

F = 25x - 9x +1